2022
DOI: 10.1186/s13063-022-06935-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of remimazolam tosylate for sedation during upper gastrointestinal endoscopy: study protocol for a multicenter randomized controlled trial

Abstract: Background Gastrointestinal endoscopy has been associated with difficult experiences and can leave patients with an unpleasant impression. Propofol and midazolam are the most commonly used intravenous anesthetics for sedation during gastrointestinal endoscopy. However, cardiac and pulmonary adverse events are the primary concerns associated with the use of these sedatives. Remimazolam tosylate is an ultra-short-acting benzodiazepine drug with a mild inhibitory effect on the respiratory and circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…At present, remimazolam had already been safely and effectively used in outpatient procedure sedation. It contributed to a more comfortable and safer experience for patients than propofol during upper gastrointestinal endoscopy [35]. Moreover, the successful completion rate of remimazolam tosilateremifentanil was non-inferior to that of dexmedetomidine-remifentanil for outpatients undergoing beroptic bronchoscopy [36].…”
Section: Discussionmentioning
confidence: 99%
“…At present, remimazolam had already been safely and effectively used in outpatient procedure sedation. It contributed to a more comfortable and safer experience for patients than propofol during upper gastrointestinal endoscopy [35]. Moreover, the successful completion rate of remimazolam tosilateremifentanil was non-inferior to that of dexmedetomidine-remifentanil for outpatients undergoing beroptic bronchoscopy [36].…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol had been previously published. 10 This multicenter, prospective, randomized single-blinded clinical trial was conducted in five university hospitals: Renji Hospital, Shanghai Jiaotong University School of Medicine (Shanghai, China), Shanghai East Hospital (Shanghai, China), The First Affiliated Hospital of Nanchang University (Nanchang, China), Affiliated Hospital of Jiaxing University (Jiaxing, China), and The Second Affiliated Hospital of Jiaxing University (Jiaxing, China). This work was approved by the Ethics Committee of Renji Hospital, Shanghai Jiao Tong University School of Medicine (approval No.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion criteria were as follows: (1) patients aged 18 to 60 yr; (2) those undergoing routine upper gastrointestinal endoscopy procedures for diagnosis and treatment; (3) those with American Society of Anesthesiologists (ASA) Physical Status I or II; (4) those with body mass index of greater than 18 kg/m 2 and less than 28 kg/m 2 ; (5) those whose time of gastroscopy did not exceed 30 min; and (6) those who clearly understand and voluntarily participated in the study and provided signed informed consent. The exclusion criteria were as follows: (1) patients who were required to undergo complicated endoscopic techniques for diagnosis and treatment; (2) those who intended to undergo tracheal intubation; (3) those who were judged to have difficulty in managing the respiratory tract; (4) those who had anemia or thrombocytopenia; (5) those diagnosed with lung diseases; (6) those diagnosed with liver and kidney diseases; (7) those with a history of drug and/or alcohol abuse within 2 yr before initiating the screening period or average daily alcohol consumption of more than 2 units of alcohol; (8) those whose blood pressure was not satisfactorily controlled by antihypertensive drugs; (9) those whose sitting systolic blood pressure was 90 mmHg or lower during the screening period; (10) pregnant or breastfeeding patients; (11) those with allergies or contraindication to benzodiazepines, opioids, propofol, and lidocaine; (12) those who participated in other drug clinical trials in the past 3 months; (13) those who were deemed unsuitable by the investigator; and (14) those diagnosed with heart disease (supplemental table 2, https://links.lww.com/ALN/D380, presents the inclusion and exclusion criteria in a detailed manner).…”
Section: Patientsmentioning
confidence: 99%
“…It is a water-soluble compound that follows first-order kinetics[ 11 , 36 , 39 , 40 ]. It undergoes metabolism by non-specific tissue esterase to an inactive compound CNS7054, independent of the dose and has a short terminal half-life (70 ± 10 minutes) (Table 1 )[ 36 , 39 - 43 ]. This allows for administration of increasing doses of the drug and prolonged continuous infusions without the possibility of enzyme saturation[ 36 ].…”
Section: Pharmacokinetics and Pharmacodynamics Of Remimazolammentioning
confidence: 99%
“…Current literature also reports a better safety profile for Remimazolam compared midazolam[ 9 , 43 ]. A phase III clinical trial was conducted to compare Remimazolam and midazolam for outpatient colonoscopy and the authors concluded that Remimazolam has faster neuropsychiatric function recovery compared to midazolam[ 9 ].…”
Section: Comparison Of Safety Of Remimazolam To Other Sedation Agentsmentioning
confidence: 99%